2021
DOI: 10.1177/19485506211041830
|View full text |Cite
|
Sign up to set email alerts
|

The Restorative Power of Nostalgia: Thwarting Loneliness by Raising Happiness During the COVID-19 Pandemic

Abstract: Lockdowns during the COVID-19 pandemic increased the risk for loneliness. We tested whether nostalgia counteracts loneliness via rises in happiness. We conducted surveys in China ( N = 1,546), the United States ( N = 1,572), and the United Kingdom ( N = 603). Although feeling lonely was associated with unhappiness, it was also associated with nostalgia, which in turn conduced to increased happiness. We complemented these findings with three experiments testing MTurk workers (Study 4, N = 209; Study 5, N = 196;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 73 publications
2
47
0
1
Order By: Relevance
“…Secondly, this study demonstrates that lack of social connectedness, loneliness, anxiety, fear, and uncertainty evoke organizational nostalgia in the pandemic era, which extends the literature on nostalgia and organizational nostalgia. For example, previous studies found that aversive states evoke nostalgia as loneliness [7], fear of death [8], lack of social connectedness [8], and anxiety [51]. Concordantly, Davis [30] also stated that nostalgia 'occurs in the context of present fears, discontents, anxieties, or uncertainties'.…”
Section: Romania Stating That They Have Not Yet Been Ablementioning
confidence: 99%
“…Secondly, this study demonstrates that lack of social connectedness, loneliness, anxiety, fear, and uncertainty evoke organizational nostalgia in the pandemic era, which extends the literature on nostalgia and organizational nostalgia. For example, previous studies found that aversive states evoke nostalgia as loneliness [7], fear of death [8], lack of social connectedness [8], and anxiety [51]. Concordantly, Davis [30] also stated that nostalgia 'occurs in the context of present fears, discontents, anxieties, or uncertainties'.…”
Section: Romania Stating That They Have Not Yet Been Ablementioning
confidence: 99%
“…Nostalgia is considered to be a predominantly positive, approach‐oriented mindset which people typically mobilize under negatively valenced conditions. An increasing amount of evidence shows that aversive stimuli, such as loneliness (Loh et al, 2021; Wildschut et al, 2006; X. Zhou et al, 2021), social exclusion (Seehusen et al, 2013), boredom (van Tilburg et al, 2013), negative mood (Barrett et al, 2010; Wildschut et al, 2006), discontinuity between one's past and present (Sedikides et al, 2008; Sedikides et al, 2015), and meaninglessness (Routledge et al, 2011, 2012) all trigger a (need for) nostalgia. And not without a reason.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The Regulatory Model was also tested in two correlational online studies conducted in Western samples during the COVID-19 pandemic (Zhou et al, 2021). Loneliness was positively associated with nostalgia, but negatively associated with well-being (e.g., happiness).…”
Section: Nostalgia As a Buffermentioning
confidence: 99%